CONVERGENCE IN ACTION: WHERE ENVIRONMENTAL SCIENCE MEETS SUSTAINABLE DEVELOPMENT PRACTICE - Herdiansyah, Herdis (Journal of Environmental Science and Sustainable Development, 2025)
Since the introduction of the Sustainable Development Goals (SDGs), the pursuit of human well-being through development and planetary sustainability for a better future has become a global discourse (de Jong & Vijge, 2021; Naseer et al., 2025; Arora-Jonsson, 2023). The SDGs have catalyzed interdisciplinary dialogue and strengthened global commitment (Naseer et al., 2025) by emphasizing the balance and integration of economic, social, and environmental aspects (Sedovs et al., 2025). However, the assumption that all goals can be achieved simultaneously and harmoniously seems hasty and potentially ignores the inherent tensions between ecological and economic interests (Spaiser et al., 2016; Glinik et al., 2024). For example, land-use changes drivened by economic growth can lead to ecosystem degradation (Luo & He, 2023). Furthermore, biodiversity degradation and the climate crisis are often frame within the logic of global capitalism to encourage economic growth (Rosales, 2008; van Niekerk, 2020). Economic growth itself is ambivalent, on the one hand promoting development, but on the other driving environmental degradation. Today's realities also show that the consistent rapid increase in industrial and service sector activity has placed enormous pressure on the environment and natural resources (Sadiq et al., 2022). In this context, the SDGs can be seen as a promising normative framework, but their implementation ultimately depends on the ability to interpret and manage the tensions between goals. Governance plays a critical role in the success of sustainable development initiatives (Filho et al., 2023; Adebayo et al., 2025; Naseer et al., 2025). Good governance ensures that policies are effectively enforced, resources are allocated efficiently, and stakeholders are adequately engaged (Handoyo, 2024). Environmental sustainability is driven by appropriate physical planning and land use, as well as ecological or biodiversity conservation (Paudel & States, 2023). The successful implementation of the SDGs will depend on untangling the complex interactions between their goals and targets (Breuer et al., 2019). An integrated approach requires both to sustainability requires simultaneously realizing the potential of its key dimensions, as well as managing the tensions, trade-offs, and synergies between them. This is where an interdisciplinary approach in environmental science becomes essential. Such an approach focuses not only on calculating environmental degradation but also on dominant narratives and reconstructing power relations. Understanding environmental risk, for example, cannot be separated from the historical, social, and political context surrounding it. Environmental risk is not simply a neutral, objective entity, but rather a construct shaped by power, knowledge, and access to decision-making. Therefore, all decisions must strive to promote positive growth and balance within natural systems (Mensah, 2019) Environmental science offers a platform that integrates scientific discussion, policy action, and community aspirations to reposition development as a reflective and participatory process. The challenge extends beyond simply collecting more data or refining indicators; it involves innovating an ethical system robust enough to manage conflicts between values, priorities, and visions of sustainability itself. Herein lies the urgency: making environmental science a space for critical reflection. The diversity of local conditions presents both challenges and opportunities in the application of global sustainability frameworks, as discussed through the diverse case studies in this issue, from soil microbial dynamics in Bangladesh (Begum et al., 2025), to the transformation of livelihoods among illegal gold miners in Indonesia (Ardikoesoema & Karuniasa, 2025). Both studies emphasize that science-based solutions can be integrated into sustainable development strategies at various scales. This geographic and methodological diversity enables a deeper understanding of how principles of sustainability practices can be contextualized locally while still contributing to global goals. The Journal of Environmental Science and Sustainable Development has been indexed by Scopus [JESSD Scopus Link] and presents various studies that demonstrate the concrete contribution of environmental science in achieving the SDGs through a multi-scale and interdisciplinary approach. The current 14th issue of the Journal of Environmental Science and Sustainable Development presents a series of studies that demonstrate the concrete contribution of environmental science at various scales in achieving the SDGs through a multi-scale and interdisciplinary approach. The articles in this issue not only support these claims empirically and rigorously but also demonstrate, in practical terms, how environmental research can be translated into effective strategies for sustainable development at the local, national, and global levels.